In the Shadow of the Asylum: Gender, Madness, and Ableism in the Reform Work of Clarissa Lathrop - Rembis, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2026)
This article contemplates ableism in historical sources and in the historical discipline through an investigation of the experiences of Clarissa Lathrop after she left the Utica, New York, insane asylum in 1882. Lathrop, like other former asylum inmates, began advocating for asylum inmates’ rights, accountability for asylum physician-administrators, and policy change immediately upon her release from the institution. She testified before the New York State Legislature twice, came together with allies to create a reform organization, wrote letters to state officials and others, travelled and spoke publicly about the need for change in America’s asylum system, and self-published her account of her experiences. She and others received support from sympathetic journalists and politicians as well as other allies. Yet Lathrop was also dismissed and treated with disdain by her contemporaries, and she was largely forgotten by later historians, who considered her both unable to speak to her own, and others’, lived experiences and incapable of advocating for change. As this article will show, a gendered ableism that, until now, has gone either unnoticed or unaddressed by historians shaped Lathrop’s rich life and legacy.